Umbelliferone and esculetin protect against N‐nitrosodiethylamine‐induced hepatotoxicity in rats. (26th April 2016) - Subramaniam, Sudhakar Raja; Ellis, Elizabeth M.
Abstract: N‐nitrosodiethylamine (NDEA), a nitrosamine compound, is known to cause liver damage through the generation of reactive oxygen species (ROS), resulting in oxidative damage to macromolecules such as DNA, and the consequent development of cancer. The present study examines the protective effects of two antioxidant coumarin compounds umbelliferone (Umb) and esculetin (Esc) against NDEA‐induced hepatotoxicity when administered in the diet to male Wistar rats. The results show that treatment with Umb (0.5% w/w) and Esc (0.5% w/w) in the diet for 7 days significantly attenuates NDEA‐induced liver damage, lowering serum alanine transaminase (ALT) levels, decreasing hepatic lipid peroxidation, and restoring total glutathione levels. To investigate the mechanism for the observed protective effect, the levels of the key protective enzymes NAD(P)H: quinone oxidoreductase 1 (NQO1), heme oxygenase (HO1), and glutathione S‐transferase Pi (GSTP1) were measured by Western blotting following Umb and Esc administration. The results showed that Umb and Esc administration significantly increased the expression of NQO1 by 3.6‐ and 2.7‐fold, HO1 by 2.7‐ and 3.2‐fold, and GSTP1 by 2.8‐ and 3.2‐fold, respectively. In conclusion, Umb and Esc are capable of protecting liver from NDEA‐induced hepatotoxicity, and this is associated with the induction of protective enzymes.